Evidence of validity for the Foot and Ankle Ability Measure (FAAM) - Martin, Robroy L; Irrgang, James J; Burdett, Ray G; Conti, Stephen F; Van Swearingen, Jessie M (Foot & ankle international, 2005)
There is no universally accepted instrument that can be used to evaluate changes in self-reported physical function for individuals with leg, ankle, and foot musculoskeletal disorders. The objective of this study was to develop an instrument to meet this need: the Foot and Ankle Ability Measure (FAAM). Additionally, this study was designed to provide validity evidence for interpretation of FAAM scores. Final item reduction was completed using item response theory with 1027 subjects. Validity evidence was provided by 164 subjects that were expected to change and 79 subjects that were expected to remain stable. These subjects were given the FAAM and SF-36 to complete on two occasions 4 weeks apart. The final version of the FAAM consists of the 21-item activities of daily living (ADL) and 8-item Sports subscales, which together produced information across the spectrum ability. Validity evidence was provided for test content, internal structure, score stability, and responsiveness. Test retest reliability was 0.89 and 0.87 for the ADL and Sports subscales, respectively. The minimal detectable change based on a 95% confidence interval was +/-5.7 and +/--12.3 points for the ADL and Sports subscales, respectively. Two-way repeated measures ANOVA and ROC analysis found both the ADL and Sports subscales were responsive to changes in status (p < 0.05). The minimal clinically important differences were 8 and 9 points for the ADL and Sports subscales, respectively. Guyatt responsive index and ROC analysis found the ADL subscale was more responsive than general measures of physical function while the Sports subscale was not. The ADL and Sport subscales demonstrated strong relationships with the SF-36 physical function subscale (r = 0.84, 0.78) and physical component summary score (r = 0.78, 0.80) and weak relationships with the SF-36 mental function subscale (r = 0.18, 0.11) and mental component summary score (r = 0.05, -0.02). The FAAM is a reliable, responsive, and valid measure of physical function for individuals with a broad range of musculoskeletal disorders of the lower leg, foot, and ankle.